REDUCING THE INFLUENCE OF THE PHOTOCELL’S SURFACE HEATING ON ITS PERFORMANCE - Asanov, Marlen; Bekirov, Eskender; Solomentsev, Oleksandr; Zaliskyi, Maksym (Proceedings of National Aviation University (archive), 2015)
The incident solar radiation is converted by the photocell not only into electrical energy, but also into thermal energy, that heats its surface. Only 6 – 20% of the incident solar radiation is used by photocell to produce electricity. The remaining energy, mainly, goes into heating the photocell. The solar energy conversion efficiency of photocells decreases in case of temperature increasing. This work is devoted to reduce the photocell’s heating effect on its solar energy conversion efficiency by installing it on additional cooling surface, which serves as a radiator. Data about the amount of solar radiation, that falls per unit area of the photocell, the ambient temperature and wind speed is taken for Simferopol city. Based on the simulation results the area of an additional cooling surface is calculated. The area of additional cooling surface A' during the year changes insignificantly, and 2 – 2.2 times bigger than the area of the photocell A. The simulation data was obtained for the ratio of additional cooling surface area to the area of the photocell A'/A. This information, according to the authors, is representative, universal and suitable for further analysis.